Wybrane czynniki ryzyka upadków wśród osób starszych mieszkających w środowisku wiejskim = Selected risk factors of fall among elderly people living in rural environment - Bartoszek, Adrian; Kocka, Katarzyna; Bartoszek, Agnieszka; Ślusarska, Barbara; Nowicki, Grzegorz; Jamrozik, Kamila (Journal of Education, Health and Sport, 2016)
Bartoszek Adrian, Kocka Katarzyna, Bartoszek Agnieszka, Ślusarska Barbara, Nowicki Grzegorz, Jamrozik Kamila. Wybrane czynniki ryzyka upadków wśród osób starszych mieszkających w środowisku wiejskim = Selected risk factors of fall among elderly people living in rural environment. Journal of Education, Health and Sport. 2016;6(8):625-636. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61044 http://ojs.ukw.edu.pl/index.php/johs/article/view/3793 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016. Wybrane czynniki ryzyka upadków wśród osób starszych mieszkających w środowisku wiejskim Selected risk factors of fall among elderly people living in rural environment Adrian Bartoszek1, Katarzyna Kocka2, Agnieszka Bartoszek2, Barbara Ślusarska2, Grzegorz Nowicki2, Kamila Jamrozik3 1Student Kierunku Lekarskiego, Wydział Lekarski, Uniwersytet Medyczny w Łodzi 2Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej , Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3Centrum Medyczne DYNMED, ul. Rynek 10, 36-065 Dynów Background Falls are one of many main geriatric problems, causing decreasing quality of life and increasing disability of people after 65. Objective The aim of this research is assessment of risk and occurrence of falls of old people living in a village and to describe factors that have influence on fall occurrence. Material and methods To research acceded 92 people after 65 years old living in a village in home environment. Tinetti test (POMA) and questionnaire were used in research. Results Respondents are exposed to external risk factors of falls such as high bath without handles, lack of non-slip mats in the bathroom, uneven surfaces, poor lighting, cables lying on the floor, rugs and uncomfortable shoes. From internal risk factors of falls the biggest influence belong to: diseases of the locomotor system, cardiovascular, defects in vision and hearing, taking five or more medications per day, fear of falling. Most commonly the seniors fall after 75 years old. Conclusions The risk of falls by the elderly people living in a village is significant. High risk and tendency of fall refer to 79 % respondents and it is caused by impose of internal and external risk factors of fall 2. High risk of fall more often refer to elderly after 75 years old, people with elementary education and living alone. Key words: elderly people, falls, risk factors, home environment. Wprowadzenie Upadki należą do wielkich problemów geriatrycznych powodując pogorszenie jakości życia oraz wzrost niepełnosprawności osób po 65 roku życia. Cel pracy - ocena ryzyka występowania upadków u osób starszych mieszkających w środowisku wiejskim oraz określenie czynników jakie mają wpływ na wystąpienie ryzyka upadku. Materiał i metoda Badaniem objęto 92 osoby starsze po 65 r.ż. mieszkających w środowisku domowym na wsi. W pracy zastosowano standaryzowane narzędzie do oceny równowagi i chodu Tinetti POMA oraz kwestionariusz ankiety . Wyniki Ankietowani są narażeni na czynniki zewnętrzne ryzyka upadku i należą do nich : wysoka wanna bez uchwytów, brak dywaników antypoślizgowych w łazience, nierówne powierzchnie, nieodpowiednie oświetlenie, kable leżące na podłodze, dywany oraz niewygodne obuwie. Wśród wewnętrznych czynników ryzyka upadkuduży wpływ miały: choroby narządu ruchu, choroby układu krążenia, wady wzroku i słuchu, przyjmowanie 5 i więcej leków dziennie, obawy przed wystąpieniem upadku. Znacznie częściej upadają osoby po 75 roku życia. Wnioski : Ryzyko upadku u osób starszych, mieszkających w środowisku wiejskim jest duże. Wysokie ryzyko upadku i skłonność do upadku dotyczy 79% badanych oraz jest spowodowane nakładaniem się wewnętrznych i zewnętrznych czynników ryzyka. Wysokie ryzyko upadku częściej występuje u osób starszych po 75r.ż. , osób z wykształceniem podstawowym i mieszkających samotnie. Słowa kluczowe: osoby starsze, upadki, czynniki ryzyka, środowisko domowe.